UJI EFEK ANTIINFLAMASI EKSTRAK n-HEKSAN PATIKAN KEBO (Euphorbia hirta L.) PADA MENCIT (Mus musculus) - Alwiyah Nur Syarif; Usmar Usmar (Jurnal Farmasi UIN Alauddin Makassar, 2014)
The research concerning the inflammation effect of   n-hexan of patikan kebo to the mice by using albumin as the udem induce. The research were devided in to 6 groups, each groups 0,1%, 0,2%, 0,4%, 0,8%. By using the NaCMC as the negative control and Acetosal as the Positif control. All the mice were induce to get udem before the treathment by 0,1 ml/gBB albumin solutio 1%  via intraplantar. The udem volume wera measured by using Plethysmometer during 60 minutes. Which the measurement interval was about 15 minutes. Data of decrease udem then doing with  statistic test of untidy perfect scheme (RAL), and then continued with Duncan test for finding out the difference of its treatment. This research has showed that patikan kebo (Euphorbia hirta L) herbs of n-heksan extract  with concentration of 0,1 % b/v till 0,8 % b/v possessing antiinflammation effect by reducing udem volume of mice of the mice foot.